Итоги раскопок поселения Студенок-5 и некоторые вопросы генезиса бондарихинской культуры - Буйнов, Ю. В. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary Yu. Buynov. Summing-up of Archeological Excavation of the Settlement Studenok-5 and Some Questions of Genesis of Bondarikhinskaya Culture This article contains summing-up of the research of the Late Bronze Age settlement Studenok-5 in the Kharkov region. On the grounds of the information on house-building, ceramics, household products and tools, the author of the article concludes that this monument has appeared in the basin of Seversky Donets in XII century B.C. in consequence of penetration of a part of tribes of Maklashevskaya culture from the east. Together with carriers of Maryanovskaya culture they have taken part in formation of Bondarikhinskaya culture.